The walls have the floor : mural journal, May '68 - Besançon, Julien, 1932-; McDonough, Tom, 1969-; Phillips, Whitney, 1983-; Vale, Henry (The MIT Press, 2018)
The graffiti of the French student and worker uprising of May 1968, capturing participatory politics in action.